Analysis of Voidage Fluctuations in Gas-Solid Bubbling Fluidized Bed Based on Kolmogorov Entropy - Feng HAN; Kunlin CONG; Jie XIANG; Qinghai LI; Yanguo ZHANG; Jing MA (发电技术)
The gas-solid flow state determines the gas-solid mixing, heat and mass transfer characteristics in the fluidized bed, and plays an important role in the design, operation and monitoring of the fluidized bed device. In a self-built cold gas-solid bubbling fluidized bed, voidage fluctuation signals were measured using the particle concentration measuring instrument at the center of the fluidized bed under different working conditions, and were analyzed by chaotic theory using Kolmogorov entropy. The influences of apparent gas velocity, static bed height and bed size were studied. It shows the apparent gas velocity has the largest influence on Kolmogorov entropy, followed by the static bed height, and the smallest is bed size.